Gender differences measured by the MATRICS consensus cognitive battery in chronic schizophrenia patients - Baohua Zhang (Nature Portfolio, 2017)
Abstract Using Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), previous study showed significant gender differences for cognitive deficits in immediate and delayed memory in schizophrenia patients. However, RBANS does not include reasoning and problem solving, and social cognition. These cognitive functions can significantly affect the outcomes and daily life in patients. This study examined the gender differences of cognition using the measurement and treatment research to improve cognition in schizophrenia (MATRICS) consensus cognitive battery (MCCB), especially focusing on reasoning and problem solving, and social cognition in schizophrenia patients. The results showed that healthy controls exemplified better cognition than patients in both genders in all examined MCCB scores. Male healthy controls had better reasoning and problem solving and working memory than females, but these gender differences were not presented in schizophrenia patients. Also, male schizophrenia patients showed worse cognition than females on social cognition, processing speed, verbal learning and visual learning. Our results support that male schizophrenia patients had more cognitive impairment than females on reasoning and problem solving, social cognition, processing speed, working memory, verbal learning and visual learning.